2002
DOI: 10.4049/jimmunol.168.6.2944
|View full text |Cite
|
Sign up to set email alerts
|

The Role of IFN in Respiratory Syncytial Virus Pathogenesis

Abstract: Formalin-inactivated respiratory syncytial virus (RSV) vaccine preparations have been shown to cause enhanced disease in naive hosts following natural infection. In this study we demonstrate a similar pattern of enhanced disease severity following primary RSV infection of IFN-nonresponsive STAT1−/− mice. STAT1−/− mice showed markedly increased illness compared with wild-type BALB/c animals following RSV inoculation despite similar lung virus titers and rates of virus clearance. Histologically, STAT1−/− animals… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

13
159
3
1

Year Published

2002
2002
2015
2015

Publication Types

Select...
6
1
1

Relationship

1
7

Authors

Journals

citations
Cited by 164 publications
(176 citation statements)
references
References 71 publications
(42 reference statements)
13
159
3
1
Order By: Relevance
“…It has been shown that RSV-infected STAT1 Ϫ/Ϫ mice have higher lung IFN-␥ levels than RSV-infected BALB/c mice at 6 d.p.i. (63). Similarly, we found that IFN-␥ levels were sixfold higher in control Ab-treated STAT1 Ϫ/Ϫ mice than control Ab-treated BALB/c mice (Fig.…”
Section: Effect Of In Vivo Anti-asgm1 Treatment Of Rsv-infected Balb/supporting
confidence: 59%
See 2 more Smart Citations
“…It has been shown that RSV-infected STAT1 Ϫ/Ϫ mice have higher lung IFN-␥ levels than RSV-infected BALB/c mice at 6 d.p.i. (63). Similarly, we found that IFN-␥ levels were sixfold higher in control Ab-treated STAT1 Ϫ/Ϫ mice than control Ab-treated BALB/c mice (Fig.…”
Section: Effect Of In Vivo Anti-asgm1 Treatment Of Rsv-infected Balb/supporting
confidence: 59%
“…Despite exhibiting profound weight loss and mortality, anti-ASGM1-Ab and control Ab-treated RSV-infected STAT1 Ϫ/Ϫ mice were able to clear infectious RSV to below plaque assay detection levels. STAT1 Ϫ/Ϫ mice exhibit Th-2-type inflammation in response to RSV infection that includes eosinophilia and neutrophilia (63). We speculate that cell types other than activated NK and T cells (e.g., neutrophils or eosinophils) may contribute to control of RSV and play a role in severe immunopathology in STAT1 Ϫ/Ϫ mice .…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…The role of IFNγ has also been explored in the HRSV mouse challenge model [47][48][49] and has been detected in lung tissue in response to acute infection with virulent PVM J3666 [50; Table 3]. IFNγ has also been associated with a "Th1/ Th2 imbalance" [51,52], and has been implicated in a variety of pathologic outcomes related to hRSV infection, including prolonged respiratory dysfunction [53], and the exaggerated inflammatory response to an earlier parenteral vaccine formulation [54,55]. The IFNγR−/− mice used in this study, originally developed by Huang and colleagues [56] have a phenotypically normal immune system, but when challenged, demonstrate increased susceptibility to vaccinia virus, listeria and mycobacteria species despite normal cytotoxic and T helper cell responses.…”
Section: Discussionmentioning
confidence: 99%
“…However, compared to the case for other severe respiratory viral infections leading to lower respiratory tract infections, IFN--γ production by peripheral blood mononuclear cells appears to be decreased in RSV disease, perhaps pointing to its role in pathogenesis [114]. STAT1 activation by both type I and type II IFNs has been shown to play an important role in establishing a protective, Th1 Ag--specific immune response to RSV infection, however, with an accompanying preferential IL--4, IL--5, and IL--13 induction [117]. Paradoxically, IL--9 depletion at the time of immunization alone alleviated disease by reducing subsequent Th2 cytokine production without a concomitant increase in IFN--γ or TNF production [119].…”
Section: Th1 Cells and Th1-related Cytokinesmentioning
confidence: 99%